A review to update the protected areas in ecuador and an analysis of their main impacts and conservation strategies (2023)
Establishing new protected areas (PAs) is one of the first steps needed to reduce habitat loss and fragmentation, protect ecosystems that are of vital importance to conserve biodiversity, and even protect traditional cultures. The correct management of a PA can be beneficial for the different forms of life found within it and can provide multiple benefits to humanity and to the continued functioning of productive ecosystems. Protected Areas act as buffers for life while serving as sanctuaries and strongholds for species in the face of climate change. Within these areas, genetic diversity is enabled to evolve in response to the pressures of natural selection. The causes of biodiversity loss include changes in land use due to agriculture and urbanization, invasive species, overexploitation, and pollution. As stipulated, the current study aims to update the National System of Protected Areas (SNAP) by applying a review of scientific and gray literature. This review presents updated information; Ecuador currently has 74 protected areas, with state, decentralized autonomous, community, and private subdivisions. The main social and environmental impacts found in the protected areas included in the SNAP are presented in a review of the existing literature. Finally, strategies are proposed to improve the management of the protected areas of the SNAP focused on strengthening the conservation of their different life forms and the responsible use of their ecosystem services through more efficient and productive spaces.